Femininity, the Picturesque, and the Canadian Landscape: The Drawings and Watercolours of Elizabeth Simcoe and Elizabeth Hale - Korda, Andrea (Atlantis)

(untitled) (Mount Saint Vincent University, 2006)
Elizabeth Simcoe and Elizabeth Hale's drawings and watercolours are primarily esteemed as early descriptions of Canada. This paper extracts additional meaning from Simcoe and Hale's pictures by addressing their gendered experiences as British women at the turn of the eighteenth century. The author argues that shifts in their conceptions of femininity are reflected in their landscapes.